2007
DOI: 10.1073/pnas.0708561104
|View full text |Cite
|
Sign up to set email alerts
|

Human G mutant causes pseudohypoparathyroidism type Ia/neonatal diarrhea, a potential cell-specific role of the palmitoylation cycle

Abstract: Pseudohypoparathyroidism type Ia (PHP-Ia) results from the loss of one allele of G s␣, causing resistance to parathyroid hormone and other hormones that transduce signals via G s. Most Gs␣mutations cause the complete loss of protein expression, but some cause loss of function only, and these have provided valuable insights into the normal function of G proteins. Here we have analyzed a mutant G s␣ (␣s-AVDT) harboring AVDT amino acid repeats within its GDP/GTP binding site, which was identified in unique patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…Cell Culture and Transfection-The rat cardiac fibroblasts (29), HEK293 cells (30), and COS7 cells (31,32) were maintained in DMEM containing 10% (v/v) fetal bovine serum. Transfections of rat cardiac fibroblasts and HEK293 cells were performed using Lipofectamine2000 (Invitrogen) via standard procedures and COS7 cells were transfected using adenovirus infection as described previously (31,32).…”
Section: Methodsmentioning
confidence: 99%
“…Cell Culture and Transfection-The rat cardiac fibroblasts (29), HEK293 cells (30), and COS7 cells (31,32) were maintained in DMEM containing 10% (v/v) fetal bovine serum. Transfections of rat cardiac fibroblasts and HEK293 cells were performed using Lipofectamine2000 (Invitrogen) via standard procedures and COS7 cells were transfected using adenovirus infection as described previously (31,32).…”
Section: Methodsmentioning
confidence: 99%
“…cAMP Assay cAMP accumulation in COS-7 cells transiently expressing WT-V2R and each V2R mutant was assayed as described previously (32)(33)(34)(35). Briefly, 1 day after transfection, cells were reseeded into 24-well plates to which [ 3 H]adenine (2 Ci/ml) was added.…”
Section: Expression Constructs Cell Culture and Transfectionmentioning
confidence: 99%
“…24 h later, the cells were washed and incubated in 0.5 ml of assay medium containing 1 mM isobutylmethylxanthine with or without the indicated concentrations of vasopressin, OPC3, or OPC4. Reactions were terminated after 30 min by removing the medium and lysing the cells in 5% trichloroacetic acid containing ATP and cAMP (1 mM (32)(33)(34)(35).…”
Section: Expression Constructs Cell Culture and Transfectionmentioning
confidence: 99%
“…G␣s redistributes to the cytoplasmic compartments following activation (34,35), and this regulatory process is critical for limiting the activation of G␣s (36,37). However, recent studies have also shown that, in response to certain receptor agonists, the internalized G␣s protein can continue to stimulate cAMP production within endosomes (38,39).…”
mentioning
confidence: 99%